HPLC and SFC enantioseparation of (±)‐Corey lactone diol: Impact of the amylose tris‐(3, 5‐dimethylphenylcarbamate) coating amount on chiral preparation. Issue 10 (19th August 2019) - Wang, Huiying; Wang, Qiuhua; Wu, Yaling; Cheng, Lingping; Zhu, Lunan; Zhu, Junchen; Ke, Yanxiong
Abstract: As an important intermediate of prostaglandins and entecavir, optically pure Corey lactone diol (CLD) has great value in the pharmaceutical industry. In this work, the enantioseparation of (±)‐CLD was evaluated using high‐performance liquid (HPLC) and supercritical fluid chromatography (SFC). In HPLC, the separations of CLD enantiomers on polysaccharide‐based chiral stationary phases with both normal phase and polar organic phase were screened. And the conditions for the enantioseparation were optimized in HPLC and SFC, including the selection of mobile phase, temperature, back‐pressure, and other conditions. More important, it was found that the chiral resolutions were greatly enhanced by the increase of the coating amount of ADMPC (amylose tris‐(3, 5‐dimethylphenylcarbamate)) under both HPLC and SFC conditions, which can lead to the increase of the productivity and the decrease of the solvent consumption. The preparations of optically pure CLD were evaluated on a semi‐preparative (2 × 25 cm) column packed with 30% ADMPC‐coated CSP under HPLC and SFC conditions. Preparative performances in terms of kkd are 1.536 kg racemate/kg CSP/day and 1.248 kg racemate/kg CSP/day in HPLC and SFC, respectively. Abstract : ■■■